Antioxidant effects after coffee enema or oral coffee consumption in healthy Thai male volunteers - S. Teekachunhatean (2018)
We designed an open-label, randomized two-phase crossover study to investigate the antioxidant effects after single and multiple doses of a coffee enema versus coffee consumed orally. Eleven healthy subjects were randomly assigned to either receive a coffee enema (3 times weekly for 6 visits) or consume ready-to-drink coffee (2 times daily for 11 days). After a washout period, subjects were switched to receive the alternate coffee procedure. Blood samples were collected at specific time points for the determination of serum levels of glutathione (GSH), malondialdehyde (MDA) and trolox equivalent antioxidant capacity (TEAC). The findings showed that either single or multiple administrations of the coffee enema or orally consumed coffee doses seemed not to produce any beneficial effects to enhance serum GSH levels or to decrease serum MDA levels over the study period of 12 days. In contrast, mean serum TEAC levels at day 12 after the coffee enema and at days 6 and 12 after oral coffee consumption were significantly reduced from their corresponding baseline values. Thus, no beneficial effects with respect to an enhancement of serum GSH and TEAC levels or a decrease in serum MDA concentrations were demonstrated after coffee enema or orally consumed ready-to-drink coffee. © The Author(s) 2012.